GRP-107 Is Weakness in Older Patients Caused by Inappropriate Drug Use?. (12th March 2013) - Jensen, LD; Hallin, M; Andersen, O; Petersen, J
Abstract : Background: The use of potentially inappropriate medicines (PIMs) is common among the older population. Inappropriate drugs as well as polypharmacy expose older people to a greater risk of adverse drug reactions, and may cause hospitalizations. Only a few studies have examined the potential influence of the use of PIMs on functional status, cognitive status, quality of life, visual acuity and handgrip strength in older people. Purpose: To evaluate the relationship between the use of PIMs and weakness measured by functional status, cognitive status, quality of life, visual acuity and handgrip strength. Materials and Methods: A longitudinal study of patients aged ≥65 years admitted to an Acute Medical Ward in Denmark. Data was collected from October–December 2011, at admission and at a follow-up visit 30 days after discharge. Data included information on social status, home care, functional status, cognitive status, handgrip strength, quality of life, visual acuity and medicines at time of follow-up, both over-the-counter medicines and those from the general practitioner. In addition data about days of hospitalisation, age, gender and comorbidities was also collected. PIMs were evaluated by a Danish list of PIMs, and polypharmacy was defined as a regular use of ≥5 drugs. The Charlson Comorbidity Index was used to categorise comorbidities. Results: Seventy-one patients (55% men) with a median age of 79 years participated. The median number of drugs was eight per person. Eighty percent were exposed to polypharmacy. PIMs occurred in 85% of the participants, and PIMs were associated with low function status (β: −1.88, p = 0.032), low handgrip strength (β: −9.82, p = 0.006) and reduced quality of life (β: −0.19, p = 0.0005), but not with morbidity as assessed by Charlson Index. Social status, home care and visual acuity were not associated with PIMs. Conclusions: PIMs are common among older people. The use of potentially inappropriate drugs has a negative impact on functional status, handgrip strength and quality of life. No conflict of interest.